PHƯƠNG PHÁP MÔ PHỎNG SỐ ĐỘNG HỌC CƠ CẤU TRONG GIA CÔNG CHÍNH XÁC BỀ MẶT CHI TIẾT QUANG - Trọng Hùng, Nguyễn; Văn Khang, Nguyễn; Minh Phương, Nguyễn (Vietnam Journal of Science and Technology, 2017)
This paper presents numerical simulation method of the kinetics structure used in optical surface parts precision grinding machine. From the research, a numerical simulation program system of relative position, velocity and acceleration of the contrivance disk and grinding disc has been set up, as well as the animation of these mechanisms in the optical parts surface precise knuckle-lever grinding machines has been created. This program system is used to study the kinematic adjustment programs in processing precise optical surface parts with knuckle-lever grinding machines and also can be valuable for the study of the kinematic knuckle-lever mechanism used in the other mechanical processing machines. The research covers problems that have not been adequately studied in published documents